PENGEMBANGAN BUKU SPESIFIK MENARIK AKTIF RELEVAN TIMELY (SMART) BERBASIS RESEARCH BASED LEARNING PADA PEMBELAJARAN IPAS UNTUK MENDUKUNG MERDEKA BELAJAR SISWA KELAS IV SD - Estuhono Estuhono; Wiwik Okta Susilawati; Izo Ira Rudini (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT Izo Ira Rudini, 2023. Development of Specific Interesting Active Relevant Timely (SMART) Specific Books Based on Research Based Learning in Science Learning to Support Independent Learning for Class IV Elementary School Students. This research is motivated by the limitations of learning media and the lack of understanding of students in the learning process at SD Negeri 01 Sitiung. Even though learning resources that use media are needed to support teaching and learning activities, so that learning objectives can be achieved. The purpose of this research was to produce Research-Based Learning Specific Interesting Active Relevant Timely (Smart) books on science learning to support independent learning for fourth grade elementary school students which are valid, practical and effective for use in learning in fourth grade elementary school. The research method used in this study is the Research and Development (R&D) method. In this study the authors only conducted simple research or research focused on development or development. The development model used is the Plomp model which consists of 3 stages, namely: preliminary research, prototype stage, and assessment phase. The validation results of Specific Books Interesting Active Relevant Timely (SMART) Based on Research Based Learning were assessed by three expert validators, namely the material/content validation results were 88.8% categorized as very valid, the language validation results were 86.6% categorized as very valid, the validation results graph 93.3% is categorized as very valid. The results of the analysis of teacher response questionnaire data assessed by two teachers obtained an average of 93% categorized as very practical. Based on the results of the One To One Evaluation trial, the student response reached 92% which was categorized as very practical, and the results of the Small Group Evaluation trial obtained 86% results which were categorized as very practical. The results of the analysis of the effectiveness of the data on fourth grade students at Public Elementary School 01 Sitiung, namely the assessment of the realm of knowledge, attitudes and skills obtained an average of 86% categorized as Effective. Keywords: Smart Books, RBL, IPAS, Independent Learning, Elementary Schools